Profile of non-communicable disease risk factors among adults in the Republic of Palau: findings of a national STEPS survey - Watson, Berry Moon (Nagoya J Med Sci, 2015)
Palau, similar to other Pacific island countries, is currently highly burdened with non-communicable diseases (NCDs). The WHO STEPS was launched in 2011 to comprehensively survey indicators for NCDs in the country. This paper aims to describe the prevalence of key NCD risk factors assessed by the survey. The WHO instrument, including behavioral, physical and biochemical measurements, was adopted to the nationwide survey for all residents aged 25 to 64 years. A cluster-based sampling method was performed to obtain a national representative data. Valid data from 2,184 individuals were selected for the analyses, of which 75% were Palauans and 19% were Filipinos. Prevalence of current cigarette smoking was 25% in men and 10% in women. Betel nut chewing with tobacco was prevalent particularly among Palauans (58% in men, 69% in women) compared to the other ethnic groups. In terms of all types of tobacco use, 60% of men and 58% of women were current users. Overweight or obesity was very common among Palauans (84% in men, 86% in women) as well as Filipinos (52% in men, 40% in women). Hypertension was found in 55% of men and 49% of women, with the stage 2 hypertension being 21% and 19%, respectively. The prevalence of diabetic level hyperglycemia was more than 20%. Raised total cholesterol was detected in 16% of men and 20% of women. This survey revealed an alarmingly high prevalence of NCD risk factors, especially tobacco use, obesity, hypertension and raised blood glucose. The data would be useful baseline information to develop effective NCD strategies in Palau.